Diagnóstico de sobrepeso, obesidad y dislipidemias en personal administrativo y de salud del Subcentro de Salud del Área No. 3 de la ciudad de Loja. - Cueva Figueroa, Anita Mishelly (2015)
Numerous reports indicate that the prevalence of obesity in adults has increased significantly in recent decades, and one of the problems encountered with increasing prevalence, is the parallel increase in complications related to their presence, including dyslipidemia. The main objective of this study was the diagnosis of overweight, obesity and dyslipidemia in Health administrative and health sub center No. 3 in the city of Loja. This is a correlational analytical study since the analysis of different variables looking statistical association was made; It is cross-sectional and cuantititativo type. The population was represented by the medical and administrative staff working in this sub-center, a total of 78 participants of which, after applying criteria of inclusion and exclusion, a sample of 60 patients (34 women-26 men) aged was obtained between 20-53 years. From the results we note that 38% of the population have alterations in BMI (overweight and obesity), 65% of these patients are female and 35% male. Likewise, 25% of the study population presented an altered lipid profile and applying inferential statistics is a direct relationship between obesity and alterations in the profile is evident. We conclude that in our study population, obesity is more prevalent in women and is associated with high risk of dyslipidemia.